SURVEY AS A METHOD FOR MARKETING RESEARCH - Maria M. Andreeva (Вестник Северо-Кавказского федерального университета)
The article describes approaches viewing questionnaire surveys as a method for marketing research, the recommended rules for developing, structuring questionnaires, as well as reveals types of questions used, especially in a format like Internet survey, also dwelling on its advantages and disadvantages.